Acute Renal Failure in Different Malignant Tumors - Radojevic-Skodric, Sanja; Bogdanovic, Ljiljana; Jovanovic, Milena; Baralic, Ivana; Dzamic, Zoran; Gordon, Ron; Ognjanovic, Simona; Basta-Jovanovic, Gordana (Current Medicinal Chemistry, 2016)
Acute renal failure (ARF) represents a severe complication of malignancies, that causes significant morbidity and mortality. ARF is a common part of multiple organ dysfunction in critically ill patients with cancer with reported mortality rates from 72% to 85% in patients who need renal replacement therapy. The pathways leading to ARF in cancer patients are common to the development of ARF in other conditions. However, certain factors leading to the development of ARF may be associated to the tumor or to the tumor therapy. The purpose of this review is to give specific aspects of renal disease in critically ill cancer patients (CICPs), to overview the causes of ARF in CICPs and to describe recent progress in the management of these complications, including treatment toxicity and bone marrow transplantation (BMT). The prevention of ARF is obligatory and therefore the possible treatments of ARF in CICPs are also discussed.
Keywords: multiple myeloma